Design Strategy for Improving Employee Retention Based on Two-Factors Theory - Naufal Ghaliya Salsabil; Winda Nur Cahyo (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
One of the most important assets of an organization is their own employee. The effect of the employee is more impactful compared to other assets such as technology, information, and finance. The importance of managing strong employee retention for increasing employee performance cannot be overstated. The purpose of the following research is to find Factors that crucially affect employee retention based on Herzberg Two-Factors Theory and develop solutions based on findings. Data gathered by conducting participatory research with company stakeholders and researchers. Hence, the study utilized Analytical Hierarchy Processing as decision making tools to identify crucial factors. Hence, based on findings Salary becoming the crucial part affecting employee retention for this case which was conducted at PT. WASABI. Therefore further development in payment methods that in accordance with the amount of product produced is needed to make sure the payment is enough and fair for production workers to maintain a good retention rate.